The Influence of Brand Equity and Relationship Quality on Repeated Purchase Intentions of Cosmetic Active Ingredients in PT XYZ - Handinata D. Lohita; Ujang Sumarwan; Popong Nurhayati (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: Indonesia's cosmetics industry is growing rapidly, driven by increasing consumer interest in beauty and skincare product. Derma-cosmetics, which treats skin problem, needs good-quality cosmetic active ingredients. In a competitive market, recurring purchases are influenced by relationship quality and brand equityPurpose: This study seeks to examine the impact of brand equity and the factors influencing relationship quality on consumer intentions to repurchase PT XYZ's cosmetic active ingredient. Furthermore, it investigates the role of relationship quality as a mediating variable between brand equity and repurchase intention.Design/methodology/approach: PT XYZ cosmetic active ingredient customers in Indonesia were evaluated in May 2024 through of 80 local industry clients via Google Forms. SEM and Partial Least Square were used to analyze in the structural model (inner model) and measurement model (outer model).Finding/result: The findings show that in PT XYZ, brand equity influences relationship quality, including satisfaction, trust, and commitment, and affects repurchase decisions. Relationship quality mediates the link between brand equity and repurchase intention.Conclusion: Enhancing brand equity and relationship quality boosts repeat purchase intentions for cosmetic active ingredients. Trust, satisfaction, and commitment among manufacturers, distributors, and customers are crucial, with relationship quality mediating brand equity’s impact on repeat purchases.Originality/value (State of the Art): This study explores brand equity and relationship quality in a B2B context, focusing on cosmetic active ingredients rather than finished products. It examines these factors impact on repeated purchase decision through distributor, providing role insight the cosmetic ingredient supply chain. Keywords: cosmetic active ingredients, B2B, brand equity, relationship quality, repeated purchase intention